2006
DOI: 10.1667/rr3489.1
|View full text |Cite
|
Sign up to set email alerts
|

Repair of DNA Damage Induced by Accelerated Heavy Ions in Mammalian Cells Proficient and Deficient in the Non-homologous End-Joining Pathway

Abstract: Human and rodent cells proficient and deficient in non-homologous end joining (NHEJ) were irradiated with X rays, 70 keV/microm carbon ions, and 200 keV/microm iron ions, and the biological effects on these cells were compared. For wild-type CHO and normal human fibroblast (HFL III) cells, exposure to iron ions yielded the lowest cell survival, followed by carbon ions and then X rays. NHEJ-deficient xrs6 (a Ku80 mutant of CHO) and 180BR human fibroblast (DNA ligase IV mutant) cells showed similar cell survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 49 publications
10
103
0
Order By: Relevance
“…A clonogenic survival assay was conducted as described previously (6). In brief, the appropriate plating density was designed to produce 20 to 40 surviving colonies in each 6-cm dish or T25 flask.…”
Section: Colony and Spheroid Formation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…A clonogenic survival assay was conducted as described previously (6). In brief, the appropriate plating density was designed to produce 20 to 40 surviving colonies in each 6-cm dish or T25 flask.…”
Section: Colony and Spheroid Formation Assaymentioning
confidence: 99%
“…High linear energy transfer (LET) particle therapy has various advantages because of the production of spread out Bragg's peaks (SOBP), which cover tumors with biologically equivalent dose distributions. Therefore, high LET heavy-ion therapy has several potential advantages over low LET photon therapy such as increased relative biological effect, reduced oxygen enhancement ratio, decreased cellcycle-dependent radiosensitivity, and induced complex DNA damage that is not easily repaired (5,6). Over the past decades, HIMAC has been successful in treating more than 5,000 cases of various human cancers and achieved promising clinical outcomes for many radioresistant tumor types, including recurrent colorectal cancer, hepatocellular carcinoma, chondroma, and sarcoma (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Recently our group and others showed that high LET IR killing more cells than low LET IR is mainly due to the inhibition of Ku-dependent NHEJ. 5,6 After induction of DSBs, proliferating cells actively slow down cell cycle progression via checkpoint activation to provide time for repair. Previously, we and others showed that IR-induced checkpoint response mainly promotes HRR and has little effect on NHEJ.…”
mentioning
confidence: 99%
“…The studies showed that clustered DSBs lesions induced by Fe particles are dif2icult to be repaired and resulting in elevated chromosome instability and enhanced cellular radiosensitivity (40,41) . The dif2iculty of repairing the clustered DSBs may due to the nature of the complex DNA damage induced by dense ionizations along the HZE particle track (19,22,(42)(43)(44)(45) . In mammalian cells, DNA DSBs are repaired mainly by two distinct pathways: nonhomologous end joining (NHEJ) and homologous recombination (HR).…”
Section: The Repair Pathways Of Clustered Dna Damage Induced By Hze Pmentioning
confidence: 99%